Progressive muscle relaxation alleviates anxiety and improves sleep quality among healthcare practitioners in a mobile cabin hospital: a pre-post comparative study in China - Luo, Yuding; Du, Juan; Wang, Junqiu; Liu, Pingchuan; Shi, Zhongli; He, Yu; Che, Guangyao; Huang, Ke; Wang, Jian (Frontiers in Psychology, 2024)
Objective To investigate the anxiety levels, sleep quality and potential risk factors of healthcare practitioners involved in the management of COVID-19 patients in a mobile cabin hospital, and further to assess the impact of progressive muscle relaxation (PMR) on their anxiety levels and sleep quality. Methods We conducted a pre-post self-controlled trial. Healthcare practitioners meeting the inclusion criteria underwent daily 30-min PMR sessions for seven consecutive days. The Pittsburgh Sleep Quality Index (PSQI) and Hamilton Anxiety Scale (HAMA) were used to assess the anxiety and sleep quality of subjects pre- and post-intervention. Statistical analysis was performed using the Wilcoxon test, Mann–Whitney U test, Kruskal-Wallis H test, and Spearman rank correlation. Results A total of 94 participants completed the study. No statistically significant differences in HAMA or PSQI total scores were observed between groups categorized based on demographic variables such as age, sex, and years of education (p > 0.05). The PSQI total score and its components (excluding sleep medication usage) exhibited a positive correlation with the HAMA total score and its psychological anxiety component (p < 0.05), and a correlation was observed between somatic anxiety manifestations and several components of the PSQI. The PSQI total scores before and after intervention were 10.0 (8.0, 13.0) and 8.0 (6.0, 9.0) respectively (p < 0.001); the HAMA total scores were 8.0 (5.0, 13.0) and 6.0 (4.0, 9.5) respectively (p < 0.001). The detection rates of poor sleep and anxiety states, along with their severity, significantly decreased post-intervention (p < 0.001). Conclusion Healthcare practitioners experience prominent anxiety and sleep issues in the mobile cabin hospital. PMR can be an effective intervention for improving the anxiety and sleep quality of healthcare professionals during support periods in the mobile cabin hospital. However, trials with larger samples are necessitated to further affirm these preliminary findings.